2007
DOI: 10.1039/b615537e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of cyclic bis- and trismelamine derivatives and their complexation properties with barbiturates

Abstract: Cyclic bis- and trismelamine derivatives were prepared from cyanuric chloride by stepwise substitutions with appropriate amines. The complexation abilities of these melamine derivatives with barbituric acid derivatives were evaluated by UV-vis spectroscopy and (1)H NMR. The structure was also confirmed by X-ray crystallography. Both the acyclic and the cyclic bismelamine derivatives formed a 1 : 1 complex via six hydrogen bonds with barbituric acid derivatives. van't Hoff analyses on the complexation of the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…While there are many solutions to this problem in Nature, there are few non-native designed systems known. We have previously reported our aqueous-phase studies on cyanurate (CA) and melamine (M) phospholipid derivatives that drive membrane chemistry via hydrogen-bonding interactions between the CA and M headgroups . There have been numerous studies on the CA-M system; though the parent compounds readily cocrystallize in a hydrogen-bonding network in water and derivatives are well-known to assemble in low dielectric solvents or when hydrophobically buried, derivative assembly generally does not occur in hydrogen-bonding solvents. , Indeed, without the phospholipid module, monoderivatived cyanurate (CA) and melamine (M) neither assemble nor inhibit interactions between the lipids in water (Figure ) . Surface multivalency of an assembled membrane provides binding avidity that greatly enhances the hydrogen-bonding interaction at the lipid−water interface. , The requisite density of CA/M modules for recognition was indicated by diminished interaction at CA-PE/M-PE concentrations of less than 70% in fluid phase (ePC) membranes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there are many solutions to this problem in Nature, there are few non-native designed systems known. We have previously reported our aqueous-phase studies on cyanurate (CA) and melamine (M) phospholipid derivatives that drive membrane chemistry via hydrogen-bonding interactions between the CA and M headgroups . There have been numerous studies on the CA-M system; though the parent compounds readily cocrystallize in a hydrogen-bonding network in water and derivatives are well-known to assemble in low dielectric solvents or when hydrophobically buried, derivative assembly generally does not occur in hydrogen-bonding solvents. , Indeed, without the phospholipid module, monoderivatived cyanurate (CA) and melamine (M) neither assemble nor inhibit interactions between the lipids in water (Figure ) . Surface multivalency of an assembled membrane provides binding avidity that greatly enhances the hydrogen-bonding interaction at the lipid−water interface. , The requisite density of CA/M modules for recognition was indicated by diminished interaction at CA-PE/M-PE concentrations of less than 70% in fluid phase (ePC) membranes.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] We have previously reported our aqueous-phase studies on cyanurate (CA) and melamine (M) phospholipid derivatives that drive membrane chemistry via hydrogen-bonding interactions between the CA and M headgroups. 9 There have been numerous studies on the CA-M system; though the parent compounds readily cocrystallize in a hydrogen-bonding network in water [10][11][12] and derivatives are well-known to assemble in low dielectric solvents [13][14][15][16] or when hydrophobically buried, 17 derivative assembly generally does not occur in hydrogen-bonding solvents. 12,[18][19][20] Indeed, without the phospholipid module, monoderivatived cyanurate (CA) and melamine (M) neither assemble nor inhibit interactions between the lipids in water (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Barbiturate derivatives have been widely used as anaesthetic, hypnotic and other therapeutic drugs [2][3][4][5][6][7][8][9][10][11]. Due to the wide applications of barbiturates in organic and medicinal chemistry, much effort has already been made in synthesizing various types of barbiturates experimentally [12][13][14][15][16][17][18][19][20][21]. For example, Volonterio et al reported a general and straightforward one-pot sequential synthesis of 1,3,5-trisubstituted barbiturates in very mild conditions [12].…”
Section: Introductionmentioning
confidence: 99%